Adrenomedullin 2 attenuates anxiety-like behaviors by increasing IGF-II in amygdala and re-establishing blood–brain barrier - Denian Wang; Zhi Yang; Pengfei Wu; Qingyan Li; Chunyan Yu; Ying Yang; Yuefan Du; Mengwei Jiang; Junpeng Ma (Translational Psychiatry)
Abstract Anxiety disorder, a prevalent mental health issue, is one of the leading causes of disability worldwide. Damage to the blood–brain barrier (BBB) is implicated in anxiety, but its regulatory mechanisms remain unclear. Herein, we show that adrenomedullin 2 (ADM2), a novel angiogenic growth factor, alleviates autistic and anxiety-like behaviors in mice. Based on transcriptome analysis and biochemical analyses, we found that ADM2 facilitates the expression of insulin-like growth factor 2 (IGF-II), which then triggers the activation of the AKT-GSK3β-mTOR signaling pathway via the IGF-II receptor (IGF-IIR), rather than the IGF-I receptor (IGF-IR). Furthermore, as evidenced by increased Evans blue staining and decreased VE-cadherin levels, the BBB exhibited dysfunction in ADM2 knockout mice with anxiety-like behaviors. In in vitro studies, ADM2 administration promoted the expression of VE-cadherin and decreased IGF-II leakage through the endothelial barrier in a BBB model. Taken together, ADM2 may alleviate anxiety-like behavior and social deficits by enhancing BBB integrity and increasing IGF-II levels in the brain. These findings highlight the potential of ADM2 as a therapeutic target for anxiety and related mental disorders.